The U.S. Dollar and the Trade Deficit : What Accounts for the Late 1990's? - Hunt, Benjamin (IMF Working Papers; Working Paper, 2003)
Based on a version of the IMF's new Global Economic Model (GEM), calibrated to analyze macroeconomic interdependence between the United States and the rest of the world, this paper asks to what extent an asymmetric productivity shock in the tradable sector of the economy may account for real exchange rate and trade balance developments in the United States in the second half of the 1990s. The paper concludes that the Balassa-Samuelson effect of such a productivity shock is only part of the story. A second shock, a broadly defined 'risk premium' shock, and some uncertainty about the persistence of both shocks are needed to match the data more satisfactorily.